Proprotein Convertase Subtilisin/Kexin Type 9 and Systemic Inflammatory Biomarker Pentraxin 3 for Risk Stratification Among STEMI Patients Undergoing Primary PCI - Zhao X; Song L; Wang Y; Li J; Zhou J; Chen R; Liu C; Zhou P; Sheng Z; Chen Y; Zhao H; Yan H (Dove Medical Press, 2021)
Xiaoxiao Zhao,1,* Li Song,1,* Ying Wang,1,* Jiannan Li,1 Jinying Zhou,1 Runzhen Chen,1 Chen Liu,1 Peng Zhou,1 Zhaoxue Sheng,1 Yi Chen,1 Hanjun Zhao,1 Hongbing Yan2 1Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Peking Union Medical College & Chinese Academy of Medical Sciences, BeiJing, People's Republic of China; 2Department of Cardiology, Fuwai Hospital Chinese Academy of Medical Sciences, ShenZhen, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongbing YanFuwai Hospital, Chinese Academy of Medical Sciences, 12 Langshan Road, Shenzhen, 518000, People's Republic of ChinaTel +86-13701339287Email hbyanfuwai2018@163.comHanjun ZhaoDepartment of Cardiology, Fuwai Hospital, Chinese Academy of Medical Sciences, No. 167, Beijing, 100037, People's Republic of ChinaTel +86-15210020808Email 15210020808@163.comBackground and Aim: The aim of prospective study was to determine the prognostic value of combined measures of plasma proprotein convertase subtilisin/kexin type 9 (PCSK9) and pentraxin 3 (PTX3) according to the culprit-plaque morphology (plaque rupture versus plaque erosion) in relation to the in patients with acute ST-elevated myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention.Methods: A total of 434 patients with STEMI aged ≥ 18 years who underwent pre-intervention OCT imaging of culprit lesions between March 2017 and March 2019 were enrolled. Finally, 235 patients who meet the inclusion criteria were enrolled and the cohort was divided into 3 groups according to PCSK9 and PTX3 levels: group A: PCSK9 < median and Pentraxin 3 (N = 72/30.6%); group B: PCSK9 ≥ median or Pentraxin 3≥ median (N = 91/38.7%); group C: PCSK9 ≥ median and Pentraxin 3≥ median (N = 72/30.6%). MACEs were defined as a composite of all-cause death, myocardial infarction (MI) recurrence, and ischemic stroke, revascularization and heart failure.Outcomes: During a median follow-up of 2.01 years, 50 patients has occurred MACE. Two-year MACE was higher in group C (23/31.9%) than in group B (16/17.6%) and group A (11/15.3%) (p = 0.028). There was a correlation between PCSK9 and PTX3 (r = 0.302, p < 0.003). In multivariable analysis adjusted for age, gender, risk factors, and serum indexes, being in group C remained independently associated with an increased risk of MACE (hazard ratio [HR]: 2.90; p = 0.010), and group B tended to have higher MACE (HR: 1.76; p = 0.172) compared with group A. Among patients with plaque erosion by OCT, group C was independently associated with an increased risk of MACE (HR: 9.04; p = 0.048) after fully adjustment. However, the significant association was absence among patients with plaque rupture.Conclusion and Relevance: This study demonstrated the usefulness of combined measures of PCSK9 and PTX3 to enhance risk stratification in patients with STEMI especially among patients with plaque erosion. Patients with elevation of both PCSK9 and PTX3 had a markedly increased risk of MACE.Keywords: pentraxin-3, PCSK9, plaque morphology characteristics, optical coherence tomography, major adverse cardiovascular events, ST-segment elevation myocardial infarction